Five-Tier Multiple-Choice Instrument for Assessing Students' Understanding of the Straight Motion - Hidayatullah; Fatni Mufit (Universitas Pendidikan Ganesha, 2023)
The misconception in the concept of straight motion is a problem that often occurs in physics learning. An assessment instrument that specifically aims to assess conceptual understanding of the concept of straight motion is not widely available. Therefore, this research aims to develop a valid and practical five-tier multiple-choice instrument for assessing students’ understanding of the concept of straight motion. This research was development/design (DR) using the Plomp model. The model was validated by three experts. The data collection instruments were observation questionnaires, student concept tests, self-evaluation sheets, validation sheets, and practicality sheets. The results of the validity analysis showed that the instrument is in a very valid category in the aspects of presentation, content, construction/graphics, and language. Then the results of the practicality analysis show that the instrument is in the categories in terms of convenience, attractiveness, efficiency, and usefulness. Based on these results, the instrument fulfills the valid and practical category for assessing students’ understanding of the concept of straight motion and is expected to be an alternative reference to enhance the quality of physics learning and other fields of science.